THE MODERATING ROLE OF HERDING BEHAVIOR IN INVESTMENT DECISION-MAKING - Pujiati, Diyah (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2025)
The future of Indonesia's financial sector greatly depends on the millennial and Gen Z generations, who currently dominate the country's workforce. The generations that have grown up in the digital era play a crucial role in driving the transformation of Indonesia's financial sector towards a more transparent, efficient, and inclusive era. The research investigates the impact of psychological biases, risk perception, illusion of control, overconfidence, and financial literacy on investment choices made by Generation Z investors living in Surabaya, East Java, Indonesia. Behavioral finance theory is the foundation for this research, explaining how mental errors and emotional components lead investors away from logical financial decisions. The research investigates herding behavior as a factor that strengthens or diminishes the influence of psychological biases. The study employed a structured survey and applied Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine data from 287 participants, revealing that risk perception and illusion of control significantly influenced investment decisions. The effects of overconfidence and financial literacy become significantly moderated by herding behavior. The study reveals complex psychological patterns in young investor behavior and recommends better financial education to help develop rational investment choices.